2007
DOI: 10.1007/s12010-007-8061-7
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Thermogravimetric Analysis For Rapid Characterization of Biomass Composition and Selection of Shrub Willow Varieties

Abstract: The cultivation of shrub willow (Salix spp.) bioenergy crops is being commercialized in North America, as it has been in Europe for many years. Considering the high genetic diversity and ease of hybridization, there is great potential for genetic improvement of shrub willow through traditional breeding. The State University of New York-College of Environmental Science and Forestry has an extensive breeding program for the genetic improvement of shrub willow for biomass production and for other environmental ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
(13 reference statements)
3
26
1
Order By: Relevance
“…A slow heating rate was selected to clearly identify model components that thermally decompose over different temperature ranges. This rate was much lower than others reported (20 • C/min) [28,34].…”
Section: Characterization and Analysis Of The Chars Generated From Thcontrasting
confidence: 70%
See 2 more Smart Citations
“…A slow heating rate was selected to clearly identify model components that thermally decompose over different temperature ranges. This rate was much lower than others reported (20 • C/min) [28,34].…”
Section: Characterization and Analysis Of The Chars Generated From Thcontrasting
confidence: 70%
“…Percent weight for each cell wall chemical component was calculated by weight loss in designated temperature ranges that correlate to the cell wall components from TGA analysis [34]. The designated temperature ranges were selected based on differential thermogravimetry (DTG) curves vs. temperature of the model cell wall components.…”
Section: Characterization and Analysis Of The Chars Generated From Thmentioning
confidence: 99%
See 1 more Smart Citation
“…TGA/DSC techniques are particularly useful for biomass characterization as biomass is a complex mixture of polymers (cellulose, hemicelluloses and lignin). Serapiglia et al (2008); Kaloustian et al (2003); Jaffe, Collins, and Mencze (2006) have shown that the dTG curves www.intechopen.com from biomass can be divided into three weight loss regions for hemicelluloses followed by cellulose and lignin. TGA is a very sensitive technique and can be used to differentiate between mutants of similar kinds of feedstocks.…”
Section: Thermogravimetric Analysis (Tga) and Differential Scanning Cmentioning
confidence: 99%
“…TGA is a very sensitive technique and can be used to differentiate between mutants of similar kinds of feedstocks. Serapiglia et al (2008) have used high throughput TGA to find the differences between various mutants of shrub willow. TGA was also used to find the total lignin content of various feedstocks (Ghetti et al 1996).…”
Section: Thermogravimetric Analysis (Tga) and Differential Scanning Cmentioning
confidence: 99%